MODELING AND ANALYSIS OF LOCAL FAILURE GRADUAL DYNAMICS OF ROLLING BEARING INNER RING (MT) - SHANG ZhiWu; PANG HaiYu; GAO MaoSheng; LIU JingYu (Jixie qiangdu)
When the rolling bearing has a local fault, it will produce a complex vibration response. From the objective reality and irregularity of the inner ring′s actual fault shape, the displacement excitation function is introduced to qualitatively analyze the gradual change of the ball position when it passes through the fault area, and a random number sequence is used to list the characteristics of the irregularity of the bottom. Considering the radial load of the bearing and the slipping phenomenon of the balls through the fault area, a bearing inner ring dynamics model of the local gradient fault is established, and the accuracy of the model is verified by comparing and analyzing the characteristic frequency values of the fault under different rotational conditions.